Fusion of the 2nd with the 3rd Cervical Vertebrae (C2-C3): A Case Series with Possible Clinical Significance - Eirini Demeneopoulou; Dorina Papa; Ilias Giotas; Angelos Nikolaou; George Tsakotos; Vasilios Karampelias; Theodore Mariolis-Sapsakos; Dimitrios Filippou; Maria Piagkou (Case Reports in Orthopedics)
Purpose. The current case series describes three cases of fusion between the 2nd cervical vertebra, the axis (C2), and the 3rd cervical vertebra (C3), creating a C2-C3 osseous complex and highlighting its morphological type of fusion (partial or complete) and morphometric details. The developmental background of this complex is emphasized, pointing out the possible clinical significance. Materials and Methods. The osseous complexes were derived from disarticulated skeletons of body donors and were collected from the osseous collection of the Anatomy Department of the Medical School of the National and Kapodistrian University of Athens. Results. Three blocked vertebral complexes (2 partial and 1 complete C2-C3 osseous masses) were identified. In two cases, the vertebral bodies were partially fused and in one case were completely fused. In the 1st case, the C2-C3 complex had fused spinous processes and distinct transverse processes. Facets were completely fused on the left and partially fused on the right side. In the 2nd case, the C2-C3 complex had partially fused vertebral bodies and distinguishable spinous processes. In the 3rd case, the C2-C3 complex had completely fused vertebral bodies, facets, laminae, and transverse and spinous processes. Conclusions. Among the three (C2-C3) fused osseous complexes, the two were partially and the one was completely ossified. The fused vertebrae were characterized by osteophytic formations (at the dens and C3 area) and osteoporotic lesions. Taking into consideration the C2-C3 fusion, and possible coexisted variants, particular caution should be made in the upper cervical area, to interpret possible neurological manifestations and to reach a safe surgical plan.